Condições de trabalho e saúde de professores pré-escolares da cidade de Pelotas. - Silva, Luciane Goulart da (2011)
the workers in education, nowadays, face problems like the increase of the students matriculated, lack of equipments and essential material or lack of maintenance of the ones that exist, lack of infrastructure and material resources, and others. The knowledge of the work conditions and their reflection in the teacher´s health, especially at those who work with childhood education, is very important to give information that helps public politician s managers to create measures that comprehend improvements, to both work environment and population involved health. Objectives: To investigate the work and health conditions of preschool teachers from the public schools in Pelotas, RS. Methodology: Descriptive study. All the preschool teachers of the city and the state will be part of this study. The collect of the data will be performed using a pretested and codified questioner, comprehend socioeconomic, demographic, work conditions and health (musculoskeletal problems, the level of physical activity, the voice problems correlated and the minor psychological disorders) variables. The instrument used to determinate the level of physical activity will be the long version of the International Physical Activity Questionnaire (IPAQ), performing an interview regarding the previous week, including questions about the frequency and duration of the realization of moderated and intense physical activity and walking. The minor psychological problems or the minor psychiatric disease will be identified by the SRQ Self-Report Questionnaire, instrument comprising 20 questions (SRQ-20) that can be answered by self-report or interview. The identification of the musculoskeletal problems will be by the report of the presence of pain or uneasiness located at the body, according to Kuorinka et al. (1987). Problems related to the voice will be investigated by the Brazilian versions of the V-RQOL (Hogikyan & Sethuraman, 1999), which received the name Qualidade de Vida em Voz QVV (Behlau et al. 2009)